PEMBERDAYAAN WANITA DAN TANAH ADAT MINANG - Azima Azima (HUMANISMA : Journal of Gender Studies, 2018)
In the Minang community, women are considered as holders of trust and all decisions related to the use of their typical land are still dependent on the decisions of the adat leaders. In another sense, a woman is justified in possessing but the property given to her is pregnant soon (Norhalim Ibrahim 2005). Indigenous women will be grouped with land ownership but in terms of power and rights to land still controlled by traditional leaders. The lack of power in the context of managing and using customary land has led to various issues that have touched indigenous lands. The issue is the issue of customary land that is not cultivated and has become widespread. Therefore, this study aims to examine how indigenous women become hindered as a result of the boundaries held by them. Therefore, in-depth interviews with customary land owners in the study area were conducted. The study found that there were a number of obstacles that hindered efforts to capture indigenous women. Because of the allocation of Enakmen Chapter 215 customary land, conflicts between trustees and tribes, it is difficult to obtain credit facilities and the location of customary land. This situation eventually pushed to the limits of efforts to wake up the economy of women. The lack of power resulting from limited property rights makes the economic empowerment of indigenous women not easy to handle. Thus some changes in the context of traditional leadership must need to think about the relevance of ownership that is more utilizing the owner, but in the same period it does not conflict with the existence of the Minang ethnic and ethnic groups.Dalam masyarakat Minang wanita dianggap sebagai pemegang amanah dan segala keputusan berkait dengan urusan pemakaian tanah khasnya masih lagi tergantung kepada keputusan pemimpin adat. Dalam erti lain, seseorang wanita itu dibenarkan memiliki tetapi hakmilik yang diberikan kepadanya adalah hamilik terhad (Norhalim Ibrahim 2005).   Wanita adat akan  diompokkan dengan pemilikan tanah tetapi dari segi kuasa dan hak terhadap tanah masih dikuasai oleh pemimpin adat.  Ketiadaan kuasa dalam konteks mengurus dan memakai tanah adat menyebabkan timbul pelbagai isu yang menyentuh tanah adat. Antaranya adalah isu tanah adat yang tidak diusahakan dan menjadi terbiar. Oleh yang demikian kajian ini bertujuan untuk meneliti bagaimana pemerkasaan wanita adat menjadi terhalang akibat daripada sekatan pegangan yang dimiliki oleh mereka.  Oleh itu indepth interview dengan pemilik tanah adat  di kawasan kajian dilakukan. Dapatan kajian mendapati terdapat beberapa halangan yang menghalang usaha untuk memperkasakan wanita adat.  Antaranya peruntukan tanah adat Enakmen Bab 215, konflik antara pemegang amanah dan keberadaan suku, kesukaran mendapatkan kemudahan kredit dan lokasi tanah adat.  Keadaan ini akhirnya mendorong kepada batasan terhadap usaha membangunkan ekonomi wanita.  Ketiadaan kuasa akibat daripada hak milik yang terhad menjadikan  usaha pemberdayaan ekonomi wanita adat menjadi tidak mudah untuk ditangani.  Oleh demikian beberapa perubahan dalam konteks kepimpinan adat harus perlu memikirkan kerelevanan pemilikan yang lebih memanfaatkan pemilik namun dalam masa yang sama tidak mempertikaian keberadaan suku dan etnik minang. Keywords: Indigenous women, empowerment, ownership of land, land ownership and pregnancy